2012
DOI: 10.1645/ge-2924.1
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Community Structure in Birds of Prey (Accipitriformes and Falconiformes) in Southern Italy

Abstract: We compared helminth communities in 6 species of birds of prey from the Calabria region of southern Italy. In total, 31 helminth taxa, including 17 nematodes, 9 digeneans, 3 acanthocephalans, and 2 cestodes, were found. All helminth species were observed in the gastrointestinal tract, except for 3 spirurid nematodes. Most of the parasite species were detected in at least 2 hosts, but 13 helminth species were found in only 1 host. At the infracommunity level, the overall species richness and Brillouin's index o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
48
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 21 publications
6
48
1
Order By: Relevance
“…Of these species, this is the first record of Neodiplostomum attenuatum, Strigea falconis, Cladotaenia globifera, Physaloptera alata, and Centrorhynchus amphibius in Turkey's common buzzard. All helminth species found in our study have been previously described as parasitizing buzzards (Kinsella et al, 1995;Sanmartin et al, 2004;Santoro et al, 2010Santoro et al, , 2012. The species richness detected in the current study (7 species) is lower than that reported in southern Italy (13 different species/genera by Santoro et al, 2010; 17 different species/genera by Santoro et al, 2012) and in Spain (13 different species/genera by Sanmartin et al, 2004).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Of these species, this is the first record of Neodiplostomum attenuatum, Strigea falconis, Cladotaenia globifera, Physaloptera alata, and Centrorhynchus amphibius in Turkey's common buzzard. All helminth species found in our study have been previously described as parasitizing buzzards (Kinsella et al, 1995;Sanmartin et al, 2004;Santoro et al, 2010Santoro et al, , 2012. The species richness detected in the current study (7 species) is lower than that reported in southern Italy (13 different species/genera by Santoro et al, 2010; 17 different species/genera by Santoro et al, 2012) and in Spain (13 different species/genera by Sanmartin et al, 2004).…”
Section: Discussioncontrasting
confidence: 69%
“…Few studies have been performed on the helminth parasites of this raptor specifically. Santoro et al (2010Santoro et al ( , 2012 conducted 2 studies in southern Italy and reported that the species prevalence rates varied between 2.8% and 100%. In a Spanish study conducted by Sanmartin et al (2004), prevalence rates were reported to be between 0.9% and 52.7%.…”
Section: Discussionmentioning
confidence: 99%
“…The first species of Dicheilonematinae in birds were described in Russia, later in Burma, India, Australia, China, Africa, North America (Mauritz & Cole, 2008). Serratospiculum species were for the first time identified in the Eurasian Kestrel (Falco tinnunculus) in Russia by Skrjabin (1915), who morphologically characterized eight species within this genus, of these Serratospiculum tendo, Serratospiculum amaculata, Serratospiculum guttatum are (Bain & Mawson, 1981;Quentin et al, 1983;Gomez et al, 1993;Lierz & Remple, 1997;Samour & Naldo, 2001;Lloyd, 2003, Kalisinska et al, 2008Santoro et al, 2012) and the most of reported cases of infection were found in the various species of falcons, including Prairie Falcon (Falco mexicanus), Peregrine Falcon (Falco peregrinus), Gyr Falcon (Falco rusticolus), Bald Eagle (Haliaeetus leucocephalus) and Cooper's Hawk (Accipiter cooperii) (Mauritz & Cole, 2008;Jones, 2006;Santoro et al, 2010;Santoro et al, 2012). Interestingly, they have also been recorded in accipiters in North America (Sterner & Espinosa, 1988;Taft et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Although this species seems to be primarily parasite of falcons, the infection may also occur in other species of raptors. For example, Serratospiculum amaculata has been reported from both Peregrine Falcons and Prairie Falcons, the Bald Eagle (Haliaeetus leucocephalus), and Cooper's Hawk (Accipiter cooperii) (Jones, 2006;Santoro et al, 2010;Santoro et al, 2012). In the birds in Australia, two other species of the nematode were identified, namely Serratospiculum guttatum in Falco longipennis and Falco peregrinus and Serratospiculum tendo in Falco peregrinus (Rose, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Arthropods, mollusks, fishes, lizards, frogs, tadpoles and mammals are the most common prey items (López et al 2005;Zimmer and Isler 2003). Usually, the generalist feeders are exposed to a greater number of potential intermediate host species, resulting in greater helminth richness when compared to a specialized consumer (Poulin 1997(Poulin , 2007Santoro et al 2012). In despite of the broad diet of T. major, a few reports about its helminths are known: Prosthogonimus ovatus (Rudolphi, 1903) Lunaschi & Drago, 2013 (Digenea: Strigeidae) and Lyperosomum oswaldoi (Travassos, 1919) (Digenea: Dicrocoeliidae) from Argentina (Travassos and Freitas 1940;Kohn and Fernandes 1972;Vicente et al 1983;Lunaschi and Drago 2013).…”
mentioning
confidence: 99%